Lead-free Solders : Materials Reliability for Electronics. - Subramanian, K. (John Wiley & Sons, 2012)
Lead-free Solders: Materials Reliability for Electronics provides a comprehensive understanding of the current state of lead-free electronic interconnects research from fundamental, applied, and manufacturing perspectives. The main thematic areas addressed include: Alloy development Composite approaches (including nanoscale reinforcements) Thermomechanical fatigue Electromigration Whisker growth Reliability under impact loading Accelerated thermal cycling Long-term reliability High temperature lead-free solders Lead-free Solders: Materials Reliability for Electronics:€Provides a comprehen.